2020
DOI: 10.1111/ajd.13283
|View full text |Cite
|
Sign up to set email alerts
|

Dietary habits in Japanese patients with chronic spontaneous urticaria

Abstract: Background: Chronic spontaneous urticaria (CSU) is defined as the spontaneously appearing weals and/or angioedema for more than 6 weeks. Dietary habits can modulate the pathogenesis of CSU. However, dietary intakes of nutrients or food in CSU patients, compared with healthy controls, have not been examined in quality and quantity. Methods: We evaluated dietary habits in adult Japanese patients with chronic spontaneous urticaria using a validated, brief-type self-administered diet history questionnaire and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…For fiber, in a retrospective cross‐sectional case–control study, Matano et al 93 noted that in Japanese adults on antihistamines with poor control of their chronic urticaria, total fiber intake was not significantly associated with Urticaria Control Test (UCT) score, although urticaria patients had significantly higher fiber intake than controls ( p = 0.01). The aforementioned study by Pretorius et al 89 found that higher maternal intakes of resistant starch were associated with higher odds of parent‐reported eczema (aOR 1.27 95% CI 1.09, 1.49, p < 0.01), doctor‐diagnosed eczema (aOR 1.19, 95% CI 1.01, 1.41, p = 0.04), and doctor‐diagnosed eczema in non‐sensitized infants (aOR 1.29, 95% CI 1.06, 1.57, p = 0.01).…”
Section: Narrative Review Of a Systematic Searchmentioning
confidence: 99%
“…For fiber, in a retrospective cross‐sectional case–control study, Matano et al 93 noted that in Japanese adults on antihistamines with poor control of their chronic urticaria, total fiber intake was not significantly associated with Urticaria Control Test (UCT) score, although urticaria patients had significantly higher fiber intake than controls ( p = 0.01). The aforementioned study by Pretorius et al 89 found that higher maternal intakes of resistant starch were associated with higher odds of parent‐reported eczema (aOR 1.27 95% CI 1.09, 1.49, p < 0.01), doctor‐diagnosed eczema (aOR 1.19, 95% CI 1.01, 1.41, p = 0.04), and doctor‐diagnosed eczema in non‐sensitized infants (aOR 1.29, 95% CI 1.06, 1.57, p = 0.01).…”
Section: Narrative Review Of a Systematic Searchmentioning
confidence: 99%
“…In a retrospective cross-sectional case–control study focusing on fiber, it was observed that Japanese adults with AD and poor antihistamine control did not show a significant association between total fiber intake and urticaria control test scores [ 114 ].…”
Section: Nutraceuticals and Atopic Dermatitis (Ad)mentioning
confidence: 99%
“…For fiber, Matano et al 53 noted that in Japanese adults on antihistamines with poor control of their chronic urticaria, total fiber intake was not significantly associated with UCT score, although urticaria patients had significantly higher fiber intake than controls (p=0.01). A review paper by Pretorius et al 49 noted that higher maternal intakes of resistant starch were associated with higher odds of parent reported eczema (aOR 1.27 95% CI 1.09, 1.49, p < 0.01), doctor diagnosed eczema (aOR 1.19, 95% CI 1.01, 1.41, p = 0.04), and doctor diagnosed eczema in non-sensitized infants (aOR 1.29, 95% CI 1.06, 1.57, p = 0.01).…”
Section: Fibermentioning
confidence: 99%